2015
DOI: 10.4141/cjps-2014-260
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting growth pattern and nitrogen economy in ancient and modern wheat varieties

Abstract: Pourazari, F., Vico, G., Ehsanzadeh, P. and Weih, M. 2015. Contrasting growth pattern and nitrogen economy in ancient and modern wheat varieties. Can. J. Plant Sci. 95: 851Á860. Nutrient availability, especially nitrogen (N) availability, is a limiting factor for crop production in many regions of the world. Modern crop varieties often produce high yields under high resource availability, whereas ancient varieties are expected to have characteristics more suitable under low resource availability. To test this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
1
2
Order By: Relevance
“…The scaling exponent between N and P found in our study is low compared to the ones reported for other plants, suggesting that P possibly was limiting growth and yield in our study. However, the scaling exponents between N and P reported for other plants are usually interpreted in relation to vegetative plant growth but not crop (grain) yields; and vegetative biomass was uncorrelated with grains biomass in our study and other investigations 30 , 31 . In addition, higher grains biomass was associated with lower P concentrations in the growing crop (Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…The scaling exponent between N and P found in our study is low compared to the ones reported for other plants, suggesting that P possibly was limiting growth and yield in our study. However, the scaling exponents between N and P reported for other plants are usually interpreted in relation to vegetative plant growth but not crop (grain) yields; and vegetative biomass was uncorrelated with grains biomass in our study and other investigations 30 , 31 . In addition, higher grains biomass was associated with lower P concentrations in the growing crop (Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, in the latter study, N-induced enhancements in gas-exchange attributes were consistent with the increases in yield of the Italian emmer wheat accessions, which contradicts our findings on the Iranian emmer wheats. The negative response of emmer wheats to N supply can be partially related to earlier findings showing lack of ability to response to N fertilizer in the ancient wheats (Castagna et al 1996, Pourazari et al 2015. The discrepancies between our results and some of the previous reports might be due partly to the use of different plant material and mode, rate, and stage of N fertilization.…”
Section: Discussioncontrasting
confidence: 68%
“…In other words, N and water are known to interact in influencing plant growth and seed and dry mass production (Kiani et al 2016). Even though suboptimal N concentrations are postulated to impose serious limitations to the photosynthetic functions and, subsequently, dry mass and seed yield production by modern varieties of many crop plants, some evidence suggests that this generalization may not be valid with less-developed ancient land races of some staple crops (Pourazari et al 2015). Furthermore, lack of sufficient water for irrigation, in one hand, and environmental concerns, such as environmental pollution due to excessive use of N, on the other, have inspired the quest for water-and N-use efficient crop species.…”
Section: Introductionmentioning
confidence: 99%